Ohio's At-Risk Student Population: A Decade of Rising Risk - Randall S. Vesely (Educational Considerations, 2013)
Educators face increasing demands to raise student achievement, to improve classroom instruction, and to demonstrate accountability in an environment of high stakes testing. However, meeting these demands is challenging in the face of numerous risk factors that jeopardize the academic success of elementary and secondary students.
Keywords: At-Risk Student; identifying; environment; elementary; secondary; students; data sources; variables; Ohio